Optimization model of economic and environmental benefits for green development of continental shale oil reservoirs based on CCUS-EOR - CHEN Shang; DU Jialin; DU Yuanhe; LIU Yeye (Youqi dizhi yu caishoulu)
To enhance the economic and environmental benefits of continental shale oil reservoir exploitation， this study， based on the whole life-cycle theory， built a green exploitation optimization model for economic and environmental benefits based on carbon dioxide capture， utilization， and storage-enhanced oil recovery （CCUS-EOR） technology. This model consists of four parts： the environmental benefit accounting model， economic benefit accounting model， comprehensive benefit accounting and sensitivity analysis， and optimization schemes. The environmental benefit accounting covers the monetization of emissions of CO2， PM， SO2， etc. The economic benefit accounting uses the cash flow method to evaluate operational costs. Local sensitivity analysis identifies key factors for targeted optimization schemes. The research combined qualitative and quantitative methods with scenario analysis. It designed various scenarios from recovery rate， carbon price， management， and policy perspectives. By comparing economic and environmental benefits across different schemes， the optimal exploitation strategy was determined. The model results show that CCUS-EOR technology significantly improves environmental benefits over economic ones. In a studied oilfield， the environmental benefit per ton of shale oil is -148.44 yuan， and the economic benefit is 239.56 yuan； the comprehensive benefit is 91.12 yuan. Sensitivity analysis shows that oil production revenue is the most impactful factor， followed by material costs and hazardous waste treatment. Some optimization schemes from the sensitivity analysis show significant effects. The model is highly applicable to oil and gas field development， such as CCUS-EOR+unconventional reservoirs and chemical flooding + low-permeability oil reservoirs.